The Mediating Role of Impulsivity in the Relationship Between Suicidal Behavior and Early Traumatic Experiences in Depressed Subjects - Dal Santo, Francesco; Carballo, Juan José; Velasco, Angela; Jiménez-Treviño, Luis; Rodríguez-Revuelta, Julia; Martínez-Cao, Clara; Caro-Cañizares, Irene; de la Fuente-Tomás, Lorena; Menéndez-Miranda, Isabel; González-Blanco, Leticia; García-Portilla, Mª Paz; Bobes, Julio; et al. (Frontiers in Psychiatry, 2020)
Background: Depressed patients with early traumatic experiences may represent a clinically and biologically distinct subtype, with worse clinical outcomes and greater risk of suicide. Since early traumatic experiences alter development of systems that regulate the stress response, increasing sensitivity to stress and mood disorders later in life, certain personality features may influence coping strategies, putting individuals with depression and a history of early traumatic experiences at greater risk of suicidal behaviour. Objective: To determine whether impulsivity mediates the relationship between early traumatic experiences and suicidal behaviour in patients with major depressive disorder (MDD). Methods: The total sample consists of 190 patients [mean age (SD) = 53.71 (10.37); females: 66.3%], with current MDD (DSM-5 criteria). The Childhood Trauma Questionnaire-Short Form (CTQ-SF), the List of Threatening Experiences (LTE), and the Barratt Impulsiveness Scale-11 (BIS-11) were used to assess childhood and adulthood adverse life events and impulsivity, respectively. We developed mediation models by bootstrap sampling methods. Results: 81 (42.6%) patients had a history of previous suicide attempts (SA). CTQ-SF-Total and BIS-11-Total scores were significantly higher in MDD patients with previous SA. Correlation analyses revealed significant correlations between the CTQ-SF-Total and BIS-11-Total, CTQ-SF-Total and HDRS-Total, and BIS-11-Total and HDRS-Total scores. Regression models found that CTQ-SF-Total, BIS-11-Total, and HDRS-Total scores were associated with SA. Mediation analyses further revealed the association between CTQ-SF-Total and SA was mediated by the indirect effect of the BIS-11-Total score (b = 0.007, 95% CI = 0.001, 0.015), after statistically controlling for sex, the HDRS-Total, and the LTE-Total. Discussion: Data suggest that impulsivity could mediate the influence of childhood trauma on suicidal behaviour. This will help understand the role of risk factors in suicidal behaviour and aid in the development of prevention interventions focused on modifiable mediators when risk factors are non-modifiable.